Ein Baum ist ein Baum ist ein Baum ... - Nordahl, Kirsten; Eggeling, Ute 1955- (Beck & Eggeling Kunstverlag, 2015)
Our daily contact with trees, the many stories that surround them as well as their powerful symbolism, have always inspired artists to choose the tree as a motif.00Despite thematically related references, this exhibition will surprise with an exciting composition of works. Their variety in technique and expression enriches and inspires the beholder, transforming the ordinary into the extraordinary.00The exhibition comprises paintings, sculptures, photographs and videos of 54 artists fom the 20th and 21st centuries with a particular focus on contemporary art.00On the occasion of the exhibition a comprehensive catalogue with texts by Herwig Guratzsch and Kirsten Nordahl will be published.